2019
DOI: 10.1093/jac/dkz422
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial anaphylaxis: the changing face of severe antimicrobial allergy

Abstract: Objectives The epidemiology, clinical characteristics and outcomes of antimicrobial-associated anaphylaxis remain ill-defined. We sought to examine antimicrobial anaphylaxis with regard to: (i) the frequency of implicated antimicrobials; (ii) attributable mortality; and (iii) referral for definitive allergy assessment. Methods This was conducted through a national retrospective multicentre cohort study at five Australian tert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 20 publications
2
8
1
Order By: Relevance
“…This has primarily been due to an absence of high sensitivity diagnostics and availability of trained specialists (38)(39)(40). Compounding this are concerns of disease-relapse related to both performing skin testing and oral challenge in the setting of disease phenotypes with associated high mortality (41)(42)(43)(44) Many patients with non-specific delayed reactions such as a mild exanthem associated with antibiotics in the face of a viral infection, have been labeled in childhood and an increasing evidence base supports ingestion challenge in this setting. (45)(46)(47) For more severe delayed and likely T-cell mediated reactions (Table 1) including DRESS, AGEP, FDE and SJS/TEN in particular, specialized testing may have an important role to provide supportive information for a causative drug and potential for cross-reactivity (1).…”
Section: Adjunctive Approaches To Aid In the Diagnosis Of Delayed Hypersensitivity Reactionsmentioning
confidence: 99%
“…This has primarily been due to an absence of high sensitivity diagnostics and availability of trained specialists (38)(39)(40). Compounding this are concerns of disease-relapse related to both performing skin testing and oral challenge in the setting of disease phenotypes with associated high mortality (41)(42)(43)(44) Many patients with non-specific delayed reactions such as a mild exanthem associated with antibiotics in the face of a viral infection, have been labeled in childhood and an increasing evidence base supports ingestion challenge in this setting. (45)(46)(47) For more severe delayed and likely T-cell mediated reactions (Table 1) including DRESS, AGEP, FDE and SJS/TEN in particular, specialized testing may have an important role to provide supportive information for a causative drug and potential for cross-reactivity (1).…”
Section: Adjunctive Approaches To Aid In the Diagnosis Of Delayed Hypersensitivity Reactionsmentioning
confidence: 99%
“…After full-text review, 37 manuscripts were included in the systematic review ( Table 4 ). Most of the primary studies (57%) were performed in USA and/or Canada [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ], followed by 10 (27%) studies performed in Asia [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ], 5 (13%) studies in Europe [ 52 , 53 , 54 , 55 , 56 ], and 1 (3%) study in Australia [ 57 ]. Overall, 17 (46%) were multicentre studies, either retrospective or retrospective/prospective [ 23 , 24 , 25 , 26 , 28 , 29 , 30 , 31 , 33 , 34 , 35 , 40 , 41 , 42 , 44 , 48 …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, 26.3% had a mismatch of knowledge regarding what they believed was the implicated medication and what was documented in hospital records [26]. Another multicentre Australian study found that nearly 30% of the anaphylaxis episodes to antimicrobials were not documented in hospital records [28]. A study in the UK showed that, of 127 general practitioners who followed up patients with ADRs after discharge, 89% had no record of patients' ADRs, having to rely on the patients themselves to provide this information [47].…”
Section: Risk Communicationmentioning
confidence: 99%
“…Amongst 80 patients with anaphylaxis reactions to non-antimicrobial medications, a large proportion of which were due to neuromuscular blocking agents in the perioperative setting; less than half (47.5%) of the cases were reported for further evaluation [ 27 ]. Similarly, in a multicentre Australian study concerning antimicrobial-related anaphylaxis episodes, only 43.7% of 222 episodes were reported to ADR management systems within respective hospitals [ 28 ].…”
Section: Variations In Adr Managementmentioning
confidence: 99%